Implementation of halal management system in a small food manufacturing enterprise for halal certification : a case study - Anis Syuhaiza binti Shohaimi (International Institution for Halal Research and Training, International Islamic University Malaysia, 2017)
The Malaysian government has been supportive of the development and expansion of small enterprises. Unfortunately, small enterprises are still plagued by low competition due to poor performance, inability to adapt to change, high cost and low productivity. Therefore, they failed to capture potentially lucrative halal food market opportunities. Hence, halal certification will be one of the strategies to help the SMEs to expand their business, without it, the industry faces challenges ahead. This study has designed and developed a management system to assist small enterprises in implementing standard requirements toward halal certification, which is the primary purpose of this study. The methods used in this thesis are qualitative and quantitative as a research strategy. Preliminary data was collected via initial assessment of the organization and participant observation where the researcher took part in the activities. The researcher assumed the role of the trainee consultant. The result of the initial assessment was used to determine strategic action plans that permit the extensive improvements, controls, training, documentation to be integrated into the operation activities such as production, purchasing, maintenance and others activities required by the halal assurance of food safety system management. This study has also shown that significant improvements especially on the new modified premise infrastructure and documentation development. Not to mention, an innovation of prototype mold was designed and developed to replace the previous mold that improves the quality and productivity of the product. The quantitative analysis results on conformance to the system implementation showed successful implementation and finally, human-related factors are also discussed in this thesis, which contributes to the effectiveness of system implementation. The major contribution of this study serves as a valuable guideline and strategic tool for new applicants pursuing halal certification and a reference to halal service providers. Finally, it provides operational guidelines for introducing halal certification standard to a wider base of SMEs food industry.